Saunders 2022-2023 clinical judgment and test-taking strategies : passing nursing school and the NCLEX exam - Silvestri, Linda Anne; Silvestri, Angela E. (St. Louis, Missouri : Elsevier, 2022)
"Saunders 2022-2023 Clinical Judgment and Test-Taking Strategies: Passing Nursing School and the NCLEX Exam, 7th Edition provides tools to help you overcome test anxiety, develop study skills, and improve test scores. You'll gain insight into key nursing areas such as clinical judgment, prioritization, leading and managing, communication, and pharmacology. In the book and on the Evolve website, 1,200 practice questions represent all question types - including alternate item formats and new Next Generation NCLEX-style test items. Written by leading NCLEX experts Linda Anne and Angela Silvestri, this essential resource offers the practical tips and realistic practice you need to succeed on any exam!"--Publisher description
Clinical judgment -- NCSBN clinical judgment measurement model -- Cognitive skills -- Alternate item formats and the next generation NCLEX (NGN) items -- Positive and negative event queries -- Questions requiring prioritization -- Leading and managing, delegating, and assignment-making questions -- Time management -- Communication questions -- Pharmacology, medication, and intravenous calculation questions -- Close-ended words -- Medical vs. nursing interventions -- Comparable or alike options -- Parts of an option -- Umbrella option -- Laboratory values -- Visualizing the information -- Client positioning -- Therapeutic diets -- Disasters
Includes bibliographical references (page 236) and index
Keywords: Nursing -- Examinations -- Study guides; Nursing Care -- methods; Nursing Process; Test Taking Skills -- methods; Examinations; Study guides; Examinations; Study guides; Examination Questions